Elements of Social and Solidarity Economy (SSE) in the Hungarian Local Development - G. Fekete, Éva (Theory, Methodology, Practice – Review of Business and Management, 2011)
There are a wide range of local Social and Solidarity Economy (SSE) initiatives in Hungary. Initiatives are aimed at rural development (LEADER), community development, ecology, employment and settlement rejuvenation. Participants are not always aware whether they are more attached to the concept of SSE than that of Local Economic Development (LED), or vice versa. No national platform encouraging the identification of shared interests and goals has been established yet. Perhaps, this is the very reason why there has been no breakthrough in government policies with a neoliberal bias. After the completion of a few non-profit employment programmes, interest in the development of local community may, going forward, bring about significant changes that can create a social and economic environment that goes well beyond tenders and facilitates self-reliance. However, only if we are familiar with the basic principles and systems of the SSE and LED can we utilise the benefits arising from local community economic development. Furthermore, in order to be able to use external help efficiently and conduct domestic and international discussions, we have to identify our position along the global spectrum.